Feasibility and Results of a Mobile Haemophilia Outpatient Care Pilot Project - Eichler, Hermann; Schleicher, Christian; Heine, Sabine; Graf, Norbert; von Mackensen, Sylvia (Hämostaseologie, 2018)
Introduction Regular visits at haemophilia treatment centres (HTCs) in rural regions are often dependent on the access to a private car due to lack of or limited availability of public means. Therefore, a mobile haemophilia outpatient care (MHOC) concept providing home visits to haemophilia patients has been developed by the Saarland HTC, which is located in a rural German region.Methods Haemophilia patients and their parents were home visited at least twice (baseline, follow-up) by trained medical staff. Socio-demographic and clinical data were collected and interviews were performed asking the patients and parents about their needs and expectations towards such a MHOC.Results Seventy-nine patients were enrolled (56 adults, 23 children), 62.0% severely affected, 48.1% on prophylaxis, with a mean age of 37.4 ± 16.4 years (17–78) and 9.8 ± 4.2 years (3–16), respectively. Median travel distance to the HTC was 43.5 km (3–200). Note that 92.4% considered an intense binding to the HTC and a MHOC concept as ‘rather/very important’ (88.6%). They expected from a MHOC to provide consulting and educating activities, support in elderhood issues and treatment. For 35.4%, a MHOC could currently provide additional support, mainly due to patient's immobility and need of consultancy. They mainly used services in terms of consultancy in social–legal affairs and support in contacting authorities.Conclusion The results of this study support the hypothesis that a MHOC concept is a needful supplement in haemophilia comprehensive care and will improve the challenging haemophilia treatment, especially for those with limited access to HTCs or with disabilities.
Keywords: haemophilia; haemophilia treatment centre; mobile home care; patient needs; adherence; adults; children